Climate assessment in the Gramame River basin, State of Paraíba, Brazil (Research, Society and Development, 2023)
The rainfall regime in Northeast Brazil is generally conditioned by mesoscale convective systems associated with cloud clusters and storms. However, these meteorological systems are subordinated to atmospheric dynamics on a synoptic scale, causing great spatial and temporal variability. The fluvial and hydrogeological regime of a region depends on the types of climates acting on them, therefore, climatological studies are important for analysing and diagnosing various environmental issues. In this context, monitoring dry and wet periods in a drainage basin gains fundamental importance for the assessment of hydrological conditions and the environmental management of public reserves. Thus, the present work aimed to use the rainfall anomaly index (IAC) to monitor dry and humid periods and their intensities in the Gramame River basin, as well as verify the meteorological systems operating on the southern coast of the State of Paraíba. so that it can provide subsidies for environmental planning and management. In this study, monthly temperature, and precipitation data from 9 stations located in the hydrographic basin of the aforementioned river were used, with a historical series of 17 years. The results showed that the Gramame River basin has been exhibiting a very characteristic behaviour throughout the historical series with relatively high rainfall rates, with minimum values exceeding 1000 mm/year. Although the historical series is relatively short, it is possible to observe an inherent balance between dry and wet years, with a small predominance of dry years.